Geochemistry and Insights into the Distribution of Biotechnological Important Fungi from the Third Pole of the World, Karakoram Mountains Range. Issue 5 (3rd May 2021) - Rafiq, Muhammad; Hassan, Noor; Hayat, Muhammad; Ibrar, Muhammad; Sajjad, Wasim; Haleem, Abdul; Maqsood-ur-Rehman, Muhammad; Raza, Agha Muhammad; Hasan, Fariha
Abstract: The Hindu Kush, Karakoram, and Himalaya (HKKH) range is called the third pole of the world due to heavy ice storage. Passu Glacier is one of the HKKH range glaciers in Pakistan. In the present study, Passu glacier is explored geochemically, recovered psychrophilic fungi, and screened for their biotechnological applications. Geochemistry of the glacial samples revealed a high amount of dissolved free amino acids (tyrosine and adenosine), major ions (acetate, Ca 2+ and Mg 2+ ), and heavy metals (Fe, Cr and Zn). A total of 27 isolated fungi belonged to 13 genera including Antrodia, Beauveria, Cladosporium, Dothideomycetes Fontanospora, Mrakia, Penicillium, Phoma, Pleosporales, Pseudeurotium, Pseudogymnoascus, Sporobolomyces and Trichoderma with the abundance of Penicillium followed by Mrakia . The majority of isolated fungi grew well at a wide range of temperature (4–37°C), while some grew at 45°C as well, pH 1–13 and in the presence of 2–26% of NaCl. Many isolates inhibited the growth of tested bacteria and fungi. The activity of Fontanospora sp. LP5 was quite promising. The study isolates also produced commercially important extracellular enzymes. The strain Sporobolomyces ruberrimus LP6 produced 6 different types of enzymes such as amylase, cellulase, deoxyribonuclease, lipase, phosphatase and protease. This study reports first-ever geochemical analysis and fungal diversity possessing the potential of producing a wide range of antimicrobial metabolites and extracellular enzymes from Passu glacier.